2012
DOI: 10.1016/j.jcm.2011.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Chiropractic management of pediatric plantar fasciitis: a case report

Abstract: Objective: The purpose of this report is to present the case of a 10-year-old football player with bilateral plantar fasciitis who improved with a multimodal conservative approach using chiropractic treatment. Clinical Features: The patient presented with bilateral plantar heel pain at the origin of the plantar fascia with a duration of 3 weeks. Intervention and Outcome: Treatment was provided for 6 visits over a 6-week period. Chiropractic care consisted of manipulative therapy, soft tissue therapy, and home … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 31 publications
0
19
0
1
Order By: Relevance
“…The authors reported that the participants demonstrated clinically meaningful improvements in pain ratings and functional improvements in Global Rating of Change Scale and Lower Extremity Functional Scale scores. 10 More recently, Daniels and Morrell 14 reported the effectiveness of using the Graston technique to perform IASTM in addition to joint manipulation to manage a 10-year-old male athlete with bilateral plantar fasciitis. Although both case-based studies would support the use of IASTM as a plan of care component for patients with CPHP, limitations when interpreting these results include the lack of a control group and the assessment of only shortterm outcomes.…”
mentioning
confidence: 99%
“…The authors reported that the participants demonstrated clinically meaningful improvements in pain ratings and functional improvements in Global Rating of Change Scale and Lower Extremity Functional Scale scores. 10 More recently, Daniels and Morrell 14 reported the effectiveness of using the Graston technique to perform IASTM in addition to joint manipulation to manage a 10-year-old male athlete with bilateral plantar fasciitis. Although both case-based studies would support the use of IASTM as a plan of care component for patients with CPHP, limitations when interpreting these results include the lack of a control group and the assessment of only shortterm outcomes.…”
mentioning
confidence: 99%
“…[33][34][35][36][37][38][39][40][41] For example, a cross-over study of 52 hockey players with ankle sprains demonstrated that ankle manipulation was associated with improved proprioception and better post-injury ankle stability. 38 There have also been a number of studies which have highlighted a benefit from manipulation in the treatment of painful hallux abductovalgus.…”
Section: Discussionmentioning
confidence: 99%
“…9 GT has been shown to increase shoulder ROM in horizontal adduction and internal rotation when applied to the posterior shoulder. 12,13 It has also been used to alleviate pain and decrease soft tissue restrictions associated with carpal tunnel syndrome, 14 DeQuervain's stenosing tenosynovitis, 15 plantar fasciitis, 16 Achilles tendinopathy, 17,18 lumbar compression fracture, 19 lateral epicondylopathy 20 and trigger thumb. 21 However, there has been no published research studying the effects GT may have on the reduction of LBP in relation to unilateral anterior or posterior innominate rotations.…”
Section: Contentsmentioning
confidence: 99%
“…50 GT has also been shown to be beneficial in other soft tissue restrictions and adhesions, tendinitis, musculoskeletal ailments and ROM restrictions. [15][16][17][18][19][20][21]51,52…”
Section: Instrument Assisted Soft Tissue Mobilizationmentioning
confidence: 99%